Diabetes mellitus and cardiac arrhythmias - L. Yu. Morgunov (Лечащий Врач)
Background. The relationship between diabetes mellitus, the development of arrhythmias and cardiac conduction disorders has not been sufficiently studied. Rhythm and conduction disorders are observed in diabetes mellitus in the form of atrial fibrillation and fluttering, ventricular tachycardia, ventricular fibrillation, sinoauricular, intraventricular and atrioventricular blockade, prolongation of the QT interval.Objective. To analyze published works on the prevalence of atrial and ventricular arrhythmias, as well as conduction disorders in patients with diabetes mellitus.Results. The analysis of studies on cardiac arrhythmias in patients with impaired carbohydrate metabolism was carried out. There is a high prevalence of atrial fibrillation in type 1 and type 2 diabetes mellitus. Diabetes mellitus is one of the most important risk factors for the development of atrial fibrillation and a predictor of its complications – stroke and thromboembolism. Diabetes mellitus increases the frequency of atrial fibrillation and other arrhythmias, and in combination with other risk factors, the frequency of life-threatening complications and the number of hospitalizations increases. Poorly compensated diabetes and concomitant diseases were associated with a higher incidence of arrhythmias. Diabetes mellitus is an independent predictor of atrioventricular block, including grade III. Prolongation of the QT interval also increases cardiovascular mortality in diabetes. The ambiguous role of hypoglycemic conditions in the development of arrhythmias is shown. Meta-analyses of the presented studies of sodium glucose cotransporter type 2 inhibitors demonstrate a decrease in the frequency of arrhythmias, especially atrial fibrillation and flutter. In cases of cardiac arrhythmias and diabetes mellitus, SGLT2i are represented by drugs with sufficiently high antiarrhythmic efficacy and having the greatest evidence base of arrhythmogenic action. The potential role of hypoglycemic drugs of various classes for the prevention of arrhythmias in patients with diabetes mellitus has been shown.Conclusion. The link between diabetes mellitus and cardiac arrhythmias is obvious, although insufficient attention is paid to this aspect. The most common arrhythmia in diabetes is atrial fibrillation, although there are any other rhythm and conduction disorders. If there are arrhythmias or to prevent the risk of their development, it is necessary to take into account the prescribed hypoglycemic therapy.